PELATIHAN PENGGUNAAN APLIKASI PENGAJUAN PENGURANGAN PAJAK BUMI DAN BANGUNAN DI BADAN PENDAPATAN DAERAH (BAPENDA) KOTA PALEMBANG - Fyarka Aura Nuridha; Muhammad Noval; Surahmat; Meivi Kusnandar; Ayu Octarina (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The increasing number of citizens applying for Property Tax (PBB) reduction in Palembang has highlighted the need for a specialized digital solution to streamline the process. To address this issue, a Property Tax Reduction Application was developed and implemented at the Regional Revenue Agency (BAPENDA) of Palembang City. Since the system is relatively new, intensive training was required to enhance users’ knowledge and skills in operating the application effectively. This community service program was carried out through collaboration between Politeknik Negeri Sriwijaya and BAPENDA Palembang City. The implementation stages consisted of an initial workshop with stakeholders, data collection, field analysis, system development, preparation of socialization materials and training modules, followed by application training, evaluation, documentation, and reporting. The training evaluation revealed significant improvements, with participants’ understanding of the application’s features and menus increasing by 80%, and their operational skills also improving by 80%. These outcomes indicate that the training successfully enhanced users’ capacity to utilize the application, thereby supporting more effective implementation of the property tax reduction system at BAPENDA Palembang City. The findings further suggest that digital applications, combined with structured training, can serve as practical solutions to improve the efficiency and transparency of public services.